Teachers' concerns about pupils' mental health in a cross‐sectional survey of a population sample of British schoolchildren. Issue 2 (21st April 2020) - Mathews, Frances; Newlove‐Delgado, Tamsin; Finning, Katie; Boyle, Christopher; Hayes, Rachel; Johnston, Patrick; Ford, Tamsin
Abstract : Background: Schools are becoming central to the identification and referral of children and young people with poor mental health. Understanding how well a teacher concern predicts mental disorder in a child or young person is important for mental health teams who need to respond to referrals. Method: This secondary analysis of the 2004 British Child and Adolescent Mental Health Survey used the first item of the Strengths and Difficulties Questionnaire (SDQ) Impact subscale to indicate concern about a child or young person's mental health. Mental disorder according to DSM IVR criteria was assessed using the multi‐informant Development and Well‐Being Assessment. We compared the proportion with and without mental disorder according to the presence or absence of teacher concern. Results: Teacher concern was moderately predictive (49% with teacher concern had a disorder) and sensitive (teacher concern present among 56% with disorder), while lack of teacher concern was highly predictive (only 5% had disorder) and specific (94% no disorder). Teacher concern was associated with significantly poorer mental health (mean teacher SDQ total difficulty score 19.6, SD 5.6 with disorder, mean 15.0; SD 5.1 if no disorder) compared to children without teacher concern (mean 9.6, SD 5.5 with disorder, and 4.9; SD 4.3 if no disorder; F (3, 5, 931) = 1527.228, p  = .001). If both teacher and parents were concerned, the child or young person was much more likely to have a disorder. Conclusion: A lack of teacher concern can reassure mental health practitioners in the vast majority of cases. While teacher concern does identify those with poorer mental health, it is only moderately predictive of a disorder. When concerned about a child or young person, discussions with parents or others who know them may help teachers identify those who most need support. Key Practitioner Message: The emphasis on schools as a major setting to provide support and identify the need for referral to specialist mental health services means service commissioners, providers and practitioners could benefit from insight into how predictive a teacher's concern is of childhood mental health conditions and how this may vary with the type of disorder If teachers are not concerned about a child, practitioners can be reassured that there is unlikely to be a significant problem with their mental health, although this will be less certain in schools whose pupils are likely to have a higher than average levels of difficulty Teacher concerns do not necessarily differentiate between clinically impairing and mild/ moderate mental health difficulties, but do identify children in poorer mental health Asking for corroboration of concern from other sources increases the strength of the association to severe mental health disorders